2008
DOI: 10.22456/2175-2745.7015
|View full text |Cite
|
Sign up to set email alerts
|

On the Development and Evaluation of a Brazilian Portuguese Discourse Parser

Abstract: Resumo: Apresentamos neste artigo o processo de desenvolvimento e avaliação de um analisador discursivo automático para o português brasileiro. Seguindo a Teoria de Estruturação Retórica, o DiZer é um sistema simbólico baseado na ocorrência de marcadores textuais, fazendo uso de templates discursivos extraídos de um corpus de textos científicos para identificar a construir a estrutura discursiva de textos. A avaliação do DiZer mostra resultados satisfatórios para textos científicos e jornalísticos, apesar do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The classification has a top-level breakdown into discourse markers, morphological, syntactic, semantic, lexical, genre and graphical features, plus heuristics specific to each relation. We started our annotation, as we explain in Section 5, by consulting previous studies for indication of what signalling devices have been found in corpora (Halliday & Hasan, 1976;Blakemore, 1987;Schiffrin, 1987;Fraser, 1990;Scott & de Souza, 1990;Dale, 1991;Blakemore, 1992;Sanders et al, 1992Sanders et al, , 1993Knott & Dale, 1994;Knott, 1996;Corston-Oliver, 1998a;Fraser, 1999;Marcu, 1999Marcu, , 2000bBateman et al, 2001;Schiffrin, 2001;Blakemore, 2002;Lapata & Lascarides, 2004;Polanyi et al, 2004;Sporleder & Lascarides, 2005;Fraser, 2006;Huong, 2007;Prasad et al, 2007;Pardo & Nunes, 2008;Sporleder & Lascarides, 2008;Teijssen et al, 2008;Fraser, 2009;Lin et al, 2009;Pitler et al, 2009;Louis et al, 2010;Prasad et al, 2010). Then, as we annotated more and more relations, we added to our classification.…”
Section: Signals For Reliable Annotationmentioning
confidence: 99%
“…The classification has a top-level breakdown into discourse markers, morphological, syntactic, semantic, lexical, genre and graphical features, plus heuristics specific to each relation. We started our annotation, as we explain in Section 5, by consulting previous studies for indication of what signalling devices have been found in corpora (Halliday & Hasan, 1976;Blakemore, 1987;Schiffrin, 1987;Fraser, 1990;Scott & de Souza, 1990;Dale, 1991;Blakemore, 1992;Sanders et al, 1992Sanders et al, , 1993Knott & Dale, 1994;Knott, 1996;Corston-Oliver, 1998a;Fraser, 1999;Marcu, 1999Marcu, , 2000bBateman et al, 2001;Schiffrin, 2001;Blakemore, 2002;Lapata & Lascarides, 2004;Polanyi et al, 2004;Sporleder & Lascarides, 2005;Fraser, 2006;Huong, 2007;Prasad et al, 2007;Pardo & Nunes, 2008;Sporleder & Lascarides, 2008;Teijssen et al, 2008;Fraser, 2009;Lin et al, 2009;Pitler et al, 2009;Louis et al, 2010;Prasad et al, 2010). Then, as we annotated more and more relations, we added to our classification.…”
Section: Signals For Reliable Annotationmentioning
confidence: 99%